Niche differentiation in a postglacial colonizer, the bank vole Clethrionomys glareolus - Escalante, Marco A; Horníková, Michaela; Marková, Silvia; Kotlík, Petr (Ecology and evolution, 2021)
Species-level environmental niche modeling has been crucial in efforts to understand how species respond to climate variation and change. However, species often exhibit local adaptation and intraspecific niche differences that may be important to consider in predicting responses to climate. Here, we explore whether phylogeographic lineages of the bank vole originating from different glacial refugia (Carpathian, Western, Eastern, and Southern) show niche differentiation, which would suggest a role for local adaptation in biogeography of this widespread Eurasian small mammal. We first model the environmental requirements for the bank vole using species-wide occurrences (210 filtered records) and then model each lineage separately to examine niche overlap and test for niche differentiation in geographic and environmental space. We then use the models to estimate past [Last Glacial Maximum (LGM) and mid-Holocene] habitat suitability to compare with previously hypothesized glacial refugia for this species. Environmental niches are statistically significantly different from each other for all pairs of lineages in geographic and environmental space, and these differences cannot be explained by habitat availability within their respective ranges. Together with the inability of most of the lineages to correctly predict the distributions of other lineages, these results support intraspecific ecological differentiation in the bank vole. Model projections of habitat suitability during the LGM support glacial survival of the bank vole in the Mediterranean region and in central and western Europe. Niche differences between lineages and the resulting spatial segregation of habitat suitability suggest ecological differentiation has played a role in determining the present phylogeographic patterns in the bank vole. Our study illustrates that models pooling lineages within a species may obscure the potential for different responses to climate change among populations.
Keywords: ecological niche modeling; Last Glacial Maximum; cryptic refugia; Myodesglareolus; intraspecific variation; MaxEnt